Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1080/15384101.2017.1325039
|View full text |Cite
|
Sign up to set email alerts
|

SGT1-HSP90 complex is required for CENP-A deposition at centromeres

Abstract: The centromere plays an essential role in accurate chromosome segregation, and defects in its function lead to aneuploidy and thus cancer. The centromere-specific histone H3 variant CENP-A is proposed to be the epigenetic mark of the centromere, as active centromeres require CENP-A–containing nucleosomes to direct the recruitment of multiple kinetochore proteins. CENP-A K124 ubiquitylation, mediated by CUL4A-RBX1-COPS8 E3 ligase activity, is required for CENP-A deposition at the centromere. However, the mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 60 publications
(78 reference statements)
1
18
0
Order By: Relevance
“…Molecular chaperones and their accessory proteins are capable of activating and folding proteins, playing important roles in the ubiquitin–proteasome pathway, and are able to maintain protein stability. Indeed, it has been shown that the chaperone protein HSP90 can regulate the E3 ligase activity of the CUL4A complex, which in turn contributes to CENP-A ubiquitylation and CENP-A deposition at the centromeres [43]. Our present data exhibited that another chaperone protein, HSC70, was able to interact with CENP-N and that knockdown of HSC70 significantly decreased the expression of CENP-N.…”
Section: Discussionsupporting
confidence: 61%
“…Molecular chaperones and their accessory proteins are capable of activating and folding proteins, playing important roles in the ubiquitin–proteasome pathway, and are able to maintain protein stability. Indeed, it has been shown that the chaperone protein HSP90 can regulate the E3 ligase activity of the CUL4A complex, which in turn contributes to CENP-A ubiquitylation and CENP-A deposition at the centromeres [43]. Our present data exhibited that another chaperone protein, HSC70, was able to interact with CENP-N and that knockdown of HSC70 significantly decreased the expression of CENP-N.…”
Section: Discussionsupporting
confidence: 61%
“…Inflammation occurring in the testes of obese men may be reflected in, and to some extent explained by, the proteomic alterations we observed. We found reduced levels of SUGT1 (alias SGT1), a cochaperone of HSP90 with roles in Akt signaling [34], centromere function [35], and regulation of NLRP3 inflammasomes [36]. Obesity is associated with increased expression of NLRP3 [37], and as the SUGT1-HSP90 complex is responsible for maintaining these inflammasomes in a repressed state, limited levels of SUGT1 could potentially lead to an aberrant immune response and auto-activation of inflammatory pathways [36].…”
Section: Discussionmentioning
confidence: 94%
“…CENP-A In Vivo Ubiquitylation Assays in vivo CENP-A ubiquitylation assays were performed as described previously (Niikura et al, 2015(Niikura et al, , and 2017). To study ubiquitylation of exogenous EYFP-CENP-A, CENP-A -/F REP-1 cells were cotransfected with the indicated expression vector(s) (Key Resources (Lamb et al, 1995) and subjected to western blot analysis with the indicated antibodies (Key Resources Table ).…”
Section: Declaration Of Interestsmentioning
confidence: 99%
“…However, there are substantive issues with the experiments that yielded these results. We published our response describing the potential problems with their results and conclusions (Niikura et al, 2017). A major caveat is that they used a fusion protein much larger than CENP-A: in the RPE-1 CENP-A À/F knockout system, the enhanced yellow fluorescent protein (EYFP) is approximately 30 kDa, and endogenous CENP-A is about 16 kDa.…”
Section: Introductionmentioning
confidence: 99%